Research on the dynamic characteristics of a wind turbine drivetrain based on different control strategies for the generator-side inverter - Shijie Zhang; Shuangshuang Jia; Yuhao Zhao; Jing Wei; Yuting Ma; Lan Wu (PLoS ONE, 2026)
Within the operational context of wind turbines (WTs), the dynamic properties of the drivetrain significantly influence the overall system stability. The implementation of both active and passive control mechanisms within a WT facilitates smooth drivetrain operation. Various methods exist for controlling WTs to ensure optimal performance. This study is focused on the drivetrain of an 8 MW WT, and vibration control is examined as the primary research objective. A dynamic model of the electromechanical system associated with the WT drivetrain is developed. This research focuses on controlling the generator inverter to reduce the difference in immediate torque between the mechanical output torque and the electromagnetic torque (ET) of a permanent magnet synchronous generator (PMSG). Additionally, this study aims to decrease the speed variation between the generator rotor and the output shaft of the gear system to enhance tracking precision. A resonant integrator is designed to introduce specific harmonics to mitigate the harmonics present in both the ET and the current of the generator, ultimately enhancing efficiency. The results of this research demonstrate that the proposed control strategy effectively reduces transverse vibrations in critical components of the gear system while suppressing harmonics in generator current and electromagnetic fields. This approach is a viable solution for the active reduction in vibrations within the WT drivetrain.